2021
DOI: 10.1186/s12916-020-01888-0
|View full text |Cite
|
Sign up to set email alerts
|

In utero Zika virus exposure and neurodevelopment at 24 months in toddlers normocephalic at birth: a cohort study

Abstract: Background In utero exposure to Zika virus (ZIKV) is known to be associated with birth defects. The impact of in utero ZIKV exposure on neurodevelopmental outcomes in early childhood remains unclear. The objective of this study was to determine the impact of in utero ZIKV exposure on neurodevelopment at 24 months of age among toddlers who were born normocephalic to women who were pregnant during the 2016 ZIKV outbreak in French territories in the Americas. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 30 publications
2
32
0
1
Order By: Relevance
“…Different from the previous study, we used infants of asymptomatic ZIKV RT-PCR and serology negative women to minimize misclassification bias; also, compared to the Bayley III scale that was used in our study, the ASQ3 has shown significant variability in sensitivity and specificity as a screening tool for neurodevelopmental anomalies but improves as the infant advances in age. Our results support the findings of Gerzson et al [17] and Grant et al [36] and highlight the importance of having an adequate unexposed control group to determine differences in outcome incidence as a critical element of causality and to reduce selection bias risk in observational studies [38].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 91%
See 2 more Smart Citations
“…Different from the previous study, we used infants of asymptomatic ZIKV RT-PCR and serology negative women to minimize misclassification bias; also, compared to the Bayley III scale that was used in our study, the ASQ3 has shown significant variability in sensitivity and specificity as a screening tool for neurodevelopmental anomalies but improves as the infant advances in age. Our results support the findings of Gerzson et al [17] and Grant et al [36] and highlight the importance of having an adequate unexposed control group to determine differences in outcome incidence as a critical element of causality and to reduce selection bias risk in observational studies [38].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 91%
“…Previous studies evaluating the neurodevelopmental outcome of normocephalic infants born to ZIKV exposed women found significant anomalies in neurodevelopment. However, these studies did not include an appropriate control group for comparison [ 12 15 , 30 32 ] or had a high risk of selection bias [ 33 36 ]. A study by Andrade et al [ 32 ] used a similar methodology to study exposed infants observing a higher rate of receptive language delay, but the absence of a control group limited the study; our study did not find any differences in receptive or expressive language between exposed and un exposed infants using the same Bayley III score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of clinical and neuroradiological CZS abnormalities at birth does not exclude future functional implications for both the affected infant as well as its family, such as seizures, hearing loss, abnormal visual function, dysphagia, sleep disorders, and neurodevelopmental impairment [ 236 , 237 ]. Prevention strategies …”
Section: Zika Virusmentioning
confidence: 99%
“…A major concern following the in utero ZIKV exposure is whether the infants born without obvious structural brain abnormalities and/or microcephaly have impairment in development. Only a few studies compared the outcomes of the normocephalic ZIKV-exposed children with those of a neurotypical control group, or with children without ZIKV infection ( Supplementary Table S3 ) ( Cardoso et al, 2019 ; Einspieler et al, 2019 ; Valdes et al, 2019 ; Gerzson et al, 2020 ; Sobral da Silva et al, 2020 ; Familiar et al, 2021 ; Grant et al, 2021 ). Six studies did not find differences between prenatal ZIKV exposure without microcephaly and the unexposed controls ( Cardoso et al, 2019 ; Einspieler et al, 2019 ; Valdes et al, 2019 ; Gerzson et al, 2020 ; Sobral da Silva et al, 2020 ; Grant et al, 2021 ).…”
Section: Congenital Zika Syndromementioning
confidence: 99%